Experimental Study on the Influence of Different Coal Species on Gas and Coal Dust Explosion - JING Guoxun, SHAO Hongyuan, WU Yulou, GUO Shaoshuai, LIU Chuang, ZHANG Shengqi (Meikuang Anquan, 2020)
To further explore the propagation law of gas coal dust explosion with different coal species involved, 3 kinds of representative coal dust were tested in a self-made semi-enclosed pipe, and the flame propagation speed, flame surface luminescence intensity and maximum explosion pressure of gas coal dust explosion were studied. The results show that the maximum explosion pressure and flame propagation velocity of gas coal dust explosion rise first and then decrease with the increase of coal dust concentration, and there is an optimal gas concentration and coal dust concentration, which makes the flame propagation speed reach the maximum and the luminous intensity reach the maximum; flame propagation speed, the maximum explosion pressure and the luminous intensity produced by the explosion are reduced by lignite, bituminous coal and anthracite in turn.